Knowledge of Patients Regarding Self Care Practice with Permanent Colostomy in a Tertiary Care Hospital in Lahore, Pakistan - Din, Saima Karam; Yaqoob, Adnan; Perveen, Kousar; Khan, Sadia (Pakistan Journal of Medical & Health Sciences, 2022)
ABSTRACT After surgery patients with intestinal colostomy have some complications and alterations in their life. This is due to lack of information and postoperative care. More over one million patients are living with permanent colostomy and the number is growing by the rate of 100 000 annually. To remove their pouch, clean the stoma and skin surrounding the stoma, empty and dispose of waste matter from the stoma, patients with a new stoma be required to master various psychomotor abilities. This descriptive cross sectional study was carried out with 76 colostomy patients. Out of 76 patients 48.7% of the patients were males and females were 51.3%. According to the findings of this study, it is concluded that 100% patients had Inadequate Self Care which is <70%. Conclusion: For such groups of patients, an education protocol should be held on regular basis, incorporating family and caregivers so that they can engage in the colostomy patient’s care. Study Design: A Descriptive Cross Sectional Study design was used. Settings: Data was acquired from a surgical department of a tertiary hospital in Lahore using a convenient sampling strategy. Study Participants: This study comprised 76 patients who had a permanent colostomy and were between the ages of 24 years to above 60 years. Results: The conclusion of the findings of this study is that 100% patients had Inadequate self care which is <70%.